A three-dimensional Jesus: an introduction to the synoptic Gospels - Black, C. Clifton (Westminster John Knox Press, 2023)
"A concise, approachable study of the New Testament's first three Gospels viewed from multiple angles-historical, sociological, literary, theological-with attention paid to their history of interpretation"--